Strategi Kreatif Daily Lifestyle sebagai Program Unggulan di MNC Channels - Reinhard, Joel; Agustrijanto , Agustrijanto (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2024)
Strategy is important in every situation, including television. Creativity is also needed when running a television program with the aim of achieving the target being achieved. Creative strategy is a concept created to achieve the goals of a television program. The purpose of this study was to determine the daily lifestyle creative strategy as a flagship program in MNC Channels. Although this program is a new program, this program has a fairly good rating. The methodology in this research is descriptive with data collection through observation and interviews. By using Peter Pringle's program strategy, namely program planning, program production, program execution and evaluation of the results of this study, it was found that the creative strategy used by the daily lifestyle program was choosing several producers with different backgrounds and of course with each different concept, present in-depth information without including gossip, and provide shows with different themes in each special episode